Fluoxetine and Ketamine Reverse the Depressive but Not Anxiety Behavior Induced by Lesion of Cholinergic Neurons in the Horizontal Limb of the Diagonal Band of Broca in Male Rat - Chen, Linghong; Ke, Yuting; Ma, Hong; Gao, Lei; Zhou, Yiying; Zhu, Huaqiang; Liu, Huifen; Zhang, Fuqiang; Zhou, Wenhua (Frontiers in Behavioral Neuroscience, 2021)
The basal forebrain cholinergic system is involved in cognitive processes, but the role of the basal forebrain cholinergic system in depression is unknown. We investigated whether a lesion of cholinergic neurons in the horizontal limb of the diagonal band of Broca (HDB) produces depressive-like behavior and whether fluoxetine or ketamine inhibits such depressive-like behaviors. Here, in rats, we used 192 IgG-saporin to eliminate the cholinergic neurons of the HDB and evaluated depressive-like behaviors using a preference test for sucrose solution and the forced swimming test. Fourteen days after the injection of 192 IgG-saporin into the HDB, the rats exhibited a significantly fewer number of choline acetyltransferase positive cell density in HDB, accompanied with neuronal loss in the entire hippocampus. Meanwhile, these rats significantly reduced preference for sucrose solution, increased immobility time in the forced swimming test, reduced locomotor activity, decreased context dependent memory in fear conditioning and the time spent in the open arms of the plus-maze. A single dose of ketamine (10 mg/kg) increased the sucrose solution consumption, reduced the immobility time in the forced swim test, and increased locomotor activity compared to vehicle-treated rats. Moreover, in rats that were continuously treated with fluoxetine (10 mg/kg/day for 11 days), the sucrose solution consumption increased, the immobility time in the forced swim test decreased, and locomotor activity increased compared to vehicle-treated rats. The present results demonstrate that a lesion of HDB cholinergic neurons results in depressive-like and anxiety-like behaviors and that antidepressants such as fluoxetine or ketamine, can reverse these depressive-like behaviors but not anxiety-like behaviors, and suggest that a lesion of HDB cholinergic neurons and followed hippocampus damage may be involved in the pathogenesis of depression.